Severe septicemia and electrolyte imbalance in a 2-month-old infant caused by Brevundimonas diminuta (Indian Journal of Case Reports, 2024)
Brevundimonas diminuta, an opportunistic Gram-negative bacterium, is increasingly recognized as a potential pathogen in clinical settings, particularly among immunocompromised individuals. We present a case of B. diminuta bacteremia in a 2-month-old male infant presenting with high-grade fever and hypocalcemic seizures. Despite initial treatment, the patient experienced recurrent seizures, leading to hospital readmission. Microbiological analysis revealed B. diminuta, sensitive to beta-lactam antibiotics and carbapenems. Prompt initiation of targeted antibiotic therapy resulted in significant clinical improvement, highlighting the importance of timely diagnosis and tailored treatment. This case underscores the evolving clinical significance of B. diminuta and emphasizes the need for heightened awareness among health-care providers for effective management of such infections, especially in pediatric patients. Further research collaboration is warranted to better understand the epidemiology and optimal treatment strategies for B. diminuta infections.